A lightweight buyer-seller watermarking protocol based on time-stamping and composite signal representation - Kumar, Ashwani; Jain, Paras; Ali, Jabir; Kumar, Shrawan; Samuel Babu, John (International Journal of Engineering and Technology, 2018)
The protocol allows a content provider to detect duplicate copy of a digital content and restrict the content provider who blames the innocent customer. This paper, proposed a lightweight protocol, which uses composite signal representation and time-stamping for watermark embedding and extraction. We have used timestamp, which tells at what time the digital content was created, signed or verified to digital watermarking algorithms and uses the composite signal representation for minimizing the overhead and bandwidth due to the use of composite signals. The suggested protocol uses composite signal representations and timestamp based methods with digital watermarking scheme for content authentication. Our watermark embedding and detection   algorithm achieves a balance between robustness and image visual quality.     Simulation results demonstrate that the algorithm used by proposed protocol has an increase robustness and good quality of watermark images as well and withstand against various image-processing attacks.